2022
DOI: 10.1128/aac.01659-21
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review of Antimalarial Drug Candidates in Phase I and II Drug Development

Abstract: The emergence and spread of parasite resistance to currently available antimalarials has highlighted the importance of developing novel antimalarials. This scoping review provides an overview of antimalarial drug candidates undergoing phase I and II studies between 1 January 2016 and 28 April 2021. PubMed, Web of Science, Embase, clinical trial registries and reference lists were searched for relevant studies. Information regarding antimalarial compound details, clinical trial characteristics, study population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…1 Although there are clinically approved antimalarial agents in use, drug resistance has spread quickly and widely, and the limited availability of antimalarials has led many researchers to seek new antimalarials. 2–4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although there are clinically approved antimalarial agents in use, drug resistance has spread quickly and widely, and the limited availability of antimalarials has led many researchers to seek new antimalarials. 2–4…”
Section: Introductionmentioning
confidence: 99%
“…1 Although there are clinically approved antimalarial agents in use, drug resistance has spread quickly and widely, and the limited availability of antimalarials has led many researchers to seek new antimalarials. [2][3][4] In Plasmodium, thiamine 1 (Fig. 1) is converted into its active form, thiamine pyrophosphate (TPP) 2, by the enzyme thiamine pyrophosphokinase (TPK).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 A successful strategy for developing low-cost, alternative therapies to improve the potency and therapeutic scope of an organic anti-infective drug is the use of metal complexes 10,11 or the addition of a ferrocenyl moiety 12 to the parent drug, as exemplified with the antimalarial ferroquine, 13,14 which successfully completed phase II clinical trials. 15,16 Importantly, we demonstrated that the replacement of one of the triazoles of FCZ by an organometallic moiety (e.g., ferrocene and ruthenocene) allowed unveiling of a subset of FCZ analogs (1a−4a, Figure 1A) more effective than the parent FCZ against various fungal strains. 17 In the present study, we expanded on our previous work and assessed the efficacy of eight newly synthesized FCZ analogs (5a−12a; Figure 1B) that are metabolically more stable than the previous series tested on a panel of clinical fungal isolates, including highly drug-resistant strains.…”
Section: ■ Introductionmentioning
confidence: 88%
“…Estimates of the PK-PD model parameters can be derived using different statistical methods. Maximum likelihood methods are widely used in the analysis of data from early phase antimalarial-drug trials [9,16]. However, these methods are limited, often failing to achieve convergence unless 10 many of the parameter values are fixed.…”
Section: Pharmacodynamic Modelmentioning
confidence: 99%
“…Drug development is a resource-heavy, expensive and time-consuming process, with only approximately 10% of drugs tested in Phase 1 trials ultimately gaining approval [8]. The journey from early phase clinical trials to Phase 3 clinical trials in patients, to then drug registration, can take many years [9]. Cipargamin is a promising candidate antimalarial drug that has transitioned from early phase studies [10] to Phase 2 clinical trials of adult patients with falciparum malaria [11, 12].…”
Section: Introductionmentioning
confidence: 99%